Prevention of hypoparathyroidism: A step-by-step near-infrared autofluorescence parathyroid identification method - Huang, Junwei; He, Yurong; Wang, Yuan; Chen, Xiao; Zhang, Yang; Chen, Xiaohong; Huang, Zhigang; Fang, Jugao; Zhong, Qi (Frontiers in Endocrinology, 2023)
Background Hypoparathyroidism is an important factor that seriously affects the quality of life of patients after thyroidectomy. This study aimed to optimize the surgical procedure for parathyroid identification using near-infrared autofluorescence (NIRAF) during thyroidectomy. Methods This was a prospective controlled study that included 100 patients with primary papillary thyroid carcinoma diagnosed in Beijing Tongren Hospital between June 2021 and April 2022 who were awaiting total thyroidectomy and bilateral neck dissection. The patients were randomly divided into an experimental group in whom step-by-step NIRAF imaging was used to identify parathyroid glands, and a control group in whom NIRAF was not used. Results The number of parathyroid glands identified in the NIRAF group was higher than that in the control group (195 vs. 161, p=0.000, Z=-5.186). The proportion of patients with parathyroid glands inadvertently removed in the NIRAF group was lower than that in the control group (2.0% vs. 18.0%, respectively; p=0.008, 2=7.111). In the NIRAF group, we found that more than 95% of the superior parathyroid glands and more than 85% of the inferior parathyroid glands were identified before the dangerous phase, which was much higher than that in the control group. The incidences of temporary hypoparathyroidism, hypocalcemia, and symptomatic hypocalcemia were higher in the control group than those in the NIRAF group. On the first postoperative day, the average parathyroid hormone (PTH) level in the NIRAF group decreased to 38.1% of the preoperative level and that in the control group decreased to 20.0% of the preoperative level (p=0.000, Z=-3.547). On the third postoperative day, the PTH level in 74% of the patients in the NIRAF group recovered to normal levels, whereas it recovered in only 38% of the patients in the control group (p=0.000, 2=13.149). The PTH levels in all patients in the NIRAF group had recovered within 30 days after surgery, whereas one patient in the control group failed to return to the normal level 6 months after surgery and was diagnosed with permanent parathyroidism. Conclusions The step-by-step NIRAF parathyroid identification method can effectively locate the parathyroid gland and protect its function.